HUBUNGAN TINGKAT AKTIVITAS FISIK DAN VISCERAL FAT DENGAN KESEHATAN MENTAL PADA REMAJA - Agustiyawan Agustiyawan; Mona Oktarina; Kiki Rezki Faradillah; Farahdina Bachtiar (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: This study aims to find out the relationship between the level of physical activity and visceral fat and mental health in adolescents. Methods: The research method used is quantitative observation with a cross-sectional approach. A total of 353 adolescents in the village of Curug will participate in the study. The parameters used are the IPAQ-SF (International Physical Activity Questionnaire Short Form) to assess the level of physical activity, performance bioelectrical impedance, and the BDI II (Beck Depression Inventory II) questionnaire to assess mental health . Results: The 353 participants (250 women [70.8%] and 103 males [29.2%]). The average age (SD) is 20.5 (± 2,05) years. The level of physical activity has a correlation with the level of visceral fat (r = 0,67, p < 0,05). However, the level is not correlated with mental health. There is a relationship between the level of physical activity and visceral fat and mental health (r = - 0,32, p < 0,05). Conclusion: There is a small but significant inverse relationship between physical activity level, visceral fat, and adolescent mental health. Future research should focus on the prospective relationship between components of visceral fat and mental health in adolescents.